1991
DOI: 10.1038/hdy.1991.17
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genetic structure within three sugar maple (Acer saccharum Marsh.) stands

Abstract: Approximately 100 trees were sampled and mapped in each of three natural Sugar Maple (Acer saccharum Marsh.) stands in northwestern Ontario. Starch-gel electrophoresis was used to resolve five polymorphic enzyme loci from bud tissue and spatial genetic structure was examined in each of the three stands using spatial autocorrelation techniques. A significant small scale genetic structure was detected in all stands and patch widths were inferred to be approximately 20-30 m. A nonrandom distribution of genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
5
10

Year Published

1992
1992
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 33 publications
10
71
5
10
Order By: Relevance
“…In European beech only a small number of significant autocorrelation values was found in a study of three natural stands in France (Merzeau et a!., 1994). Similar results were obtained in other forest tree species: Picea mariana (Knowles, 1991), Acer saccharum (Perry & Knowles, 1991), Quercus petraea and Q. robur (Bacilieri ci' a!., 1994). Studies with intensive sampling of relatively limited areas also revealed scarce spatial structuring in lodgepole pine (Epperson & Allard, 1989), Picea abies (Leonardi et al, 1996) and Turkey oak (Berg & Hamrick, 1995).…”
supporting
confidence: 65%
“…In European beech only a small number of significant autocorrelation values was found in a study of three natural stands in France (Merzeau et a!., 1994). Similar results were obtained in other forest tree species: Picea mariana (Knowles, 1991), Acer saccharum (Perry & Knowles, 1991), Quercus petraea and Q. robur (Bacilieri ci' a!., 1994). Studies with intensive sampling of relatively limited areas also revealed scarce spatial structuring in lodgepole pine (Epperson & Allard, 1989), Picea abies (Leonardi et al, 1996) and Turkey oak (Berg & Hamrick, 1995).…”
supporting
confidence: 65%
“…Os estudos sobre a estrutura genética espacial de populações de plantas têm revelado padrões diferenciados. Há os que obtém estruturação moderada em faixas curtas de distância e atribuem tal fato à dispersão limitada de pólen e sementes, à reprodução vegetativa e à seleção variando espacialmente (Perry & Knowles 1991, Schnabel et al 1991, Loiselle et al 1995, Shapcott 1995. Há estudos que não encontraram evidências de estruturação (Leonardi & Menozzi 1996, Doligez & Joly 1997.…”
Section: Resultsunclassified
“…Sokal & Oden (1978b) dão um exemplo de união de diferentes estágios de vida em uma mesma análise, não sendo prejudicadas as conclusões, antes o contrário, o padrão de distribuição dos diferentes estágios pôde explicar determinadas estruturações. Há ainda, estudos que utilizam árvores maduras (Perry & Knowles 1991, Schnabel et al 1991, Leonardi & Menozzi 1996, sem especificar o estágio dos indivíduos e trabalhos que utilizam somente árvores adultas (Loiselle et al 1995, Doligez & Joly 1997. Epperson & Alvarez-Buylla (1997) analisam três estágios diferentes de vida (plântulas, juvenis e adultos) de uma espécie arbórea pioneira tropical, porém, o fazem separadamente.…”
Section: Methodsunclassified
See 2 more Smart Citations